TRUST AS A VIRTUAL TEAM EFFECTIVENESS FACTOR - O. L. Belova; L. V. Kozhevnikova; I. E. Starovoytova (Вестник университета)
A relatively new phenomenon in management practice – a virtual team has been considered. Based on a study of a wide range of domestic and foreign sources, it has been shown, what problems arise during the formation and operation of virtual teams. Attention on the problem of mutual trust in the team has been focused. It has been concluded that the lack of common social norms and opportunities for mutual control, the lack of direct personal contacts, cross-cultural problems, and the lack of informal communication impede confidence building. However, the rapid idealization of a communication partner, the ability to create the effect of physical presence with minimal means can contribute to building trust and team spirit. The article is addressed to specialists in the field of personnel management and all interested in modern technologies of labor management.